Calcium Ionophore (A23187) Rescues the Activation of Unfertilized Oocytes After Intracytoplasmic Sperm Injection and Chromosome Analysis of Blastocyst After Activation - Xu, Ziwen; Yao, Guidong; Niu, Wenbin; Fan, Huiying; Ma, Xueshan; Shi, Senlin; Jin, Haixia; Song, Wenyan; Sun, Yingpu (Frontiers in Endocrinology, 2021)
Calcium is a crucial factor in regulating the biological behavior of cells. The imbalance of calcium homeostasis in cytoplasm will cause abnormal behavior of cells and the occurrence of diseases. In intracytoplasmic sperm injection (ICSI) cycle, the dysfunction of oocyte activation caused by insufficient release of Ca2+ from endoplasmic reticulum is one of the main reasons for repeated fertilization failure. Calcium ionophore (A23187) is a highly selective calcium ionophore, which can form stable complex with Ca2+ and pass through the cell membrane at will, effectively increasing intracellular Ca2+ levels. It has been reported that calcium ionophore (A23187) can activate oocytes and obtain normal embryos. However, there are few studies on unfertilized oocytes after A23187 rescue activation of ICSI. These unfertilized oocytes still have a certain developmental potential and research value. The purpose of this study was to analyze the effects of calcium ionophore (A23187) rescue activation on the activation of unfertilized oocytes, embryonic development potential, embryonic development timing and chromosomal aneuploidy, and to compare and analyze the clinical data of patients with calcium ionophore (A23187) activation in clinical application. The results showed that a certain proportion of high-quality blastocysts with normal karyotype could be obtained after calcium ionophore (A23187) rescue activation of unfertilized oocytes, and it did not have a significant effect on the timing of embryo development. In clinical practice, direct activation with A23187 after ICSI was better than rescue activation the next day. In conclusions, the studies on the effectiveness and safety of calcium ionophore (A23187) rescue activation for oocytes with ICSI fertilization failure can enable some patients to obtain usable, high-quality embryos during the first cycle of ICSI and provide precious human embryo resources for related scientific research.